Case Report: Intravascular papillary endothelial hyperplasia in the superficial temporal artery - Cong, Rui; Shi, Shasha; Li, Yang; Xuan, Jianyuan (Frontiers in Surgery, 2025)
Intravascular papillary endothelial hyperplasia is a rare benign vascular lesion that typically occurs in thrombosed dilated veins or vascular tumors, with its occurrence within arterial blood vessels being uncommon. In this report, we present a case of intravascular papillary endothelial hyperplasia within superficial temporal artery in a 35-year-old Chinese male patient. The patient initially noticed a non-tender pulsatile mass in his left temple three years ago, which has gradually increased in size over time. Ultrasound examination revealed a well-defined, hypoechoic oval lesion in the left temporal region, with a blood vessel traversing through it and connecting to the superficial temporal artery. Complete excision of the mass was performed, and histological examination confirmed intravascular papillary endothelial hyperplasia. We provide an extensive literature review on intravascular papillary endothelial hyperplasia tumor along with a discussion on ultrasound findings.